Language and logical thinking structures in the normally hearing and deaf - Millar, Daphne Elizabeth (Department of Psychology, 2016)
The performance of twelve deaf subjects with an extremely poor comprehension of language and control over language structure, was compared with that of a normally hearing control group on four tasks of formal thinking. Six deaf subjects performed at the formal operational level on at least one task, supporting the hypothesis that formal thinking can develop to its primary formation in the severely linguistically deprived. The implications of the findings for certain cognitive theories and for educational practice are presented.